AB0936 The effect of the severity of psoriasis on screening for latent tuberculosis: A comparison study between psoriasis and rheumatoid arthritis patients. (23rd January 2014) - Wollman, J.; Madar-Balakinski, N.; Arad, U.; Reitblat, T.; Goldsmith, T.; Matz, H.; Wigler, I.; Levartovsky, D.; Paran, D.; Caspi, D.; Elkayam, O.
Abstract : Background: Screening for latent tuberculosis (TB) is mandatory before treatment with TNFα blockers. It has been suggested that latent TB based on tuberculin skin test (TST) may be over diagnosed due to Koebner phenomenon in patients with psoriasis. Objectives: To assess the effect of the extent of skin and joint involvement on the diagnosis of latent TB and to compare the TST and QuantiFERON-TB Gold (QTF-G) in patients with psoriasis (PSO) and psoriatic arthritis (PsA) to rheumatoid arthritis (RA) patients. Methods: Forty-one PSO patients (35 with PsA) and 35 RA patients candidates to receive TNF α were prospectively evaluated for TST, QTF-G, risk factors for latent TB as well as for the severity of the underlying diseases using psoriasis activity severity index (PASI) and the number of painful and swollen joints. Results: 41 PSO patients (mean age 49.7, 48% women, 36% treated with MTX) were compared to 35 RA patients (mean age 60 (p=0.006), 70% women, 70% treated with MTX (p=0.02)). No differences were observed in the mean TST (5±6.7 for PSO, 5.8±6.3 for RA), the proportion of positive TST based on 5mm as well as 10 mm, the proportion of QTF-G positive patients (7.2% in PSO vs 12% in RA). The level of agreement between TST and QTF-G was similar between the 2 groups (using TST 5 and TST 10, 74% and 81% for PSO vs 60% and 76% for RA, respectively). Furthermore, no correlation was found between the extent of psoriasis involvement evaluated by PASI and the TST, QTF-G, and the level of agreement between them. The number of tender and swollen joints, the use of MTX or corticosteroids did not affect the diagnosis of screening TB Conclusions: The extent of severity of psoriasis does not affect the results of TST and QTF-G in patients with psoriasis. The level of agreement between TST and QTF-G was similar in RA and PSO. Although it remains to be determined with test is preferable in the diagnosis of latent TB, whether the patient suffers from PSO/PsA or RA does not seem to play an important role in this choice. Disclosure of Interest: None Declared